RANCANG BANGUN APLIKASI PENGADAAN BARANG DINAS KEBUDAYAAN DAN PARIWISATA KABUPATEN BOGOR BERBASIS WEBSITE - Hanafi Eko Darono (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2021)
The goods procurement system at the Bogor Regency Culture and Tourism Office is still carried out conventionally so that it is still difficult to find data on goods that have been purchased. The system cannot find out the existence of office goods because the number of goods are not in accordance with procurement, especially regarding to the preparation of reports, namely procurement recapitulation report is not effective. Because of these conditions, it is very necessary to have a procurement application as a work aid in data processing and procurement reports. This research IS conducted to provide alternative solutions by referring to the need of business and employees relationship activities. The expected result is that the application can be used for procurement of goods at the Department of Culture and Tourism based on the website and it can be applied directly to the working field in order to facilitate the effectiveness of performance and minimize the level of errors.